Groupness, cohesion, and intention to return to sport: A study of intact youth teams - Spink, K. S.; McLaren, C. D.; Ulvick, J. D. (International Journal of Sports Science & Coaching, 2018)
The positive benefits for youth participating in sport have been well documented. Yet, keeping athletes returning to sport has been a concern. While various factors have been examined to explain this attrition, facets of the sport group experience have started to emerge. From a group perspective, it has been established that athlete intentions to return to a sport team the following season are positively associated with perceived team cohesion. While cohesion is a key group construct, other group factors are worthy of examination. The purpose of the current study was to build upon the research base by examining whether the relationship between cohesion and intention to return would be moderated by another group factor—the level of groupness ascribed to the team. At the end of a competitive season, youth soccer athletes (N=156) completed measures of task cohesion, groupness, and intention to return to their team in the future. Results revealed that the task cohesion-intention to return relationship was significantly moderated by groupness, p=.03. Simple slopes analysis revealed that the strongest relationship between task cohesion and intention to return occurred under conditions of lower groupness. These initial results indicated that intention to return was highest when the team was perceived as higher in task cohesion, regardless of groupness perceptions. However, when the team was perceived to be lower in task cohesion, those who perceived their team as being more like a group indicated a greater willingness to return to the team in the future.